2022
DOI: 10.1108/ijem-01-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

The path from social and organizational resources to satisfaction: the mediating role of academic engagement and the moderating role of psychological capital

Abstract: PurposeThis study draws on the Job Demands-Resources (JD-R) model to analyze if (1) social and organizational resources impact students' satisfaction, via academic engagement, and (2) psychological capital moderates the mediating path.Design/methodology/approachTo test our hypotheses, the authors collected data from two well-established higher education institutions (HEIs), in which 840 students participated.FindingsAdditionally, the results demonstrated that the indirect relationship between resources and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Existing studies confirmed the beneficial effects of organizational strategies on the key indicators of school outcomes (Kang & Wu, 2022;Silva et al, 2022). The organizational resources were directed to students' academic engagement, which in turn, affected their satisfaction (Silva et al, 2022).…”
Section: Organizational Strategiesmentioning
confidence: 86%
“…Existing studies confirmed the beneficial effects of organizational strategies on the key indicators of school outcomes (Kang & Wu, 2022;Silva et al, 2022). The organizational resources were directed to students' academic engagement, which in turn, affected their satisfaction (Silva et al, 2022).…”
Section: Organizational Strategiesmentioning
confidence: 86%
“…Based on the motivational process and reciprocity principle, job resources received by an employee help them complete their tasks and satisfy their basic needs of autonomy, competence, and relatedness, which lead to engagement and concomitant attitudes and behaviours (Schaufeli, 2017;Gouldner, 1960). Previous literature has examined the mediating role of employee engagement between job resources such as autonomy, feedback, social support, innovative culture, and growth opportunities and the resulting attitudes and behaviours of job satisfaction, organisational commitment, turnover intentions, task performance, and OCB (Albrecht & Marty, 2020;Bakker & Demerouti, 2014;Junça Silva et al, 2022;Naveed et al, 2022).…”
Section: Organisational Citizenship Behaviour (Ocb)mentioning
confidence: 99%